Plasma Metabolites From Choline Pathway and Risk of Cardiovascular Disease in the PREDIMED (Prevention With Mediterranean Diet) Study - Guasch‐Ferré, Marta (J Am Heart Assoc, 2017)
BACKGROUND: The relationship between plasma concentrations of betaine and choline metabolism and major cardiovascular disease (CVD) end points remains unclear. We have evaluated the association between metabolites from the choline pathway and risk of incident CVD and the potential modifying effect of Mediterranean diet interventions. METHODS AND RESULTS: We designed a case‐cohort study nested within the PREDIMED (Prevention With Mediterranean Diet) trial, including 229 incident CVD cases and 751 randomly selected participants at baseline, followed up for 4.8 years. We used liquid chromatography–tandem mass spectrometry to measure, at baseline and at 1 year of follow‐up, plasma concentrations of 5 metabolites in the choline pathway: trimethylamine N‐oxide, betaine, choline, phosphocholine, and α‐glycerophosphocholine. We have calculated a choline metabolite score using a weighted sum of these 5 metabolites. We used weighted Cox regression models to estimate CVD risk. The multivariable hazard ratios (95% confidence intervals) per 1‐SD increase in choline and α‐glycerophosphocholine metabolites were 1.24 (1.05–1.46) and 1.24 (1.03–1.50), respectively. The baseline betaine/choline ratio was inversely associated with CVD. The baseline choline metabolite score was associated with a 2.21‐fold higher risk of CVD across extreme quartiles (95% confidence interval, 1.36–3.59; P<0.001 for trend) and a 2.27‐fold higher risk of stroke (95% confidence interval, 1.24–4.16; P<0.001 for trend). Participants in the higher quartiles of the score who were randomly assigned to the control group had a higher risk of CVD compared with participants in the lower quartile and assigned to the Mediterranean diet groups (P=0.05 for interaction). No significant associations were observed for 1‐year changes in individual plasma metabolites and CVD. CONCLUSIONS: A metabolite score combining plasma metabolites from the choline pathway was associated with an increased risk of CVD in a Mediterranean population at high cardiovascular risk. CLINICAL TRIAL REGISTRATION: URL: http://www.controlled-trials.com. Unique identifier: ISRCTN35739639.